A case of antithyroid drug‐induced agranulocytosis from a second antithyroid drugs (ATD) administration in a relapsed Graves' disease patient who was tolerant to the first ATD treatment. Issue 9 (10th July 2018) - Kim, Hyunsam; Lee, Jeongmin; Ha, Jeonghoon
Key Clinical Message: Agranulocytosis is a rare side effect of antithyroid drugs (ATD) that usually develops within the first 3‐6 months after starting treatment. We present a 64‐year‐old patient who developed agranulocytosis after starting ATD to treat relapsed Graves' disease. This patient had tolerated the first course of ATD for 72 months. This was an unusual case in which a serious side effect developed during a second ATD course. It is essential that clinicians remain vigilant to the fact that antithyroid drugs can induce agranulocytosis several years after initiated. Abstract : Agranulocytosis is a rare side effect of antithyroid drugs (ATD) that usually develops within the first 3‐6 months after starting treatment. We present a 64‐year‐old patient who developed agranulocytosis after starting ATD to treat relapsed Graves' disease. This patient had tolerated the first course of ATD for 72 months. This was an unusual case in which a serious side effect developed during a second ATD course. It is essential that clinicians remain vigilant to the fact that antithyroid drugs can induce agranulocytosis several years after initiated.